PENGARUH KOMPETENSI PROFESIONAL DAN DISIPLIN KERJA TERHADAP KINERJA GURU DENGAN GAYA KEPEMIMPINAN TRANSFORMASIONAL SEBAGAI MODERASI - Shervaneela Devinta; Agus Budi Santosa (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
This study aims and is useful to examine and analyze the impact of professional competence, work discipline, and transformational leadership on teacher performance, and whether professional competence and work discipline on teacher performance can be moderated by transformational leadership. The purpose of this research is to explain, as well as expand from previous research, namely about how the influence of professional competence and work discipline on teacher performance with transformational leadership as moderating. The sample in this study was obtained using a simple random sampling technique in the form of a questionnaire. The object of this research is all PNS Teachers of State Junior High Schools in Pekalongan City. This research shows the product that: (1). Professional competence has a positive and significant effect on teacher performance, (2). Work Discipline has a positive and significant effect on teacher performance, (3). Transformational leadership has a negative and significant effect on teacher performance, (4) Transformational leadership cannot moderate the effect between professional competence on teacher performance, (5). Transformational leadership cannot moderate work discipline on teacher performance.